Analysis of The Selection of Modes of Transportation for The Latuhalat-Mardika Route in Ambon City - Jeniffer Jill Dwi Putri; Sammy G. M. Amaheka; Juliet G. Metekohy (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Transportation has an important role in supporting community mobility, especially on the Latuhalat-Mardika route in Ambon City which connects coastal areas with city centers. Various modes of transportation are used by the community, ranging from online motorcycle taxis, private motorcycles, conventional motorcycle taxis, public transportation, to private cars. This study aims to analyze the factors that affect the choice of transportation modes and estimate the probability of choosing modes on these routes. The research method used was a quantitative method with a survey approach of 500 respondents, which was determined using the Slovin formula with purposive sampling technique. Data were analyzed using multiple linear regression and multinomial logistic regression with the help of SPSS version 26. The variables studied included cost, travel time, convenience, security, and ease of access. The results showed that security factors (82–86%) and ease of access (80–85%) were the main determinants influencing the choice of transportation modes. Meanwhile, the factors of cost, travel time, and convenience did not have a significant effect. Probability analysis shows that private motorcycles are the most dominant mode chosen (43%), followed by public transportation (29%), private cars (10%), and online motorcycle taxis and conventional motorcycle taxis (9%). Thus, people prioritize a sense of security and ease of obtaining fashion in their daily travel.